2014
DOI: 10.1158/1078-0432.ccr-13-1663
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting Small Cell Lung Cancer Harboring PIK3CA Mutation with a Selective Oral PI3K Inhibitor PF-4989216

Abstract: Purpose: Constitutive activation of phosphoinositide 3-kinase (PI3K) occurs frequently in many human tumors via either gene mutation in the p110a catalytic subunit of PI3K or functional loss of tumor suppressor PTEN. Patients with small-cell lung cancer (SCLC) have very poor prognosis and survival rates such that an effective targeted therapy is in strong demand for these patients. In this study, we characterized the highly selective oral PI3K inhibitor, PF-4989216, in preclinical SCLC models to investigate wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 43 publications
1
28
1
Order By: Relevance
“…The growth of five bladder cancer cell lines could be inhibited by pictilisib to some extent, but only PIK3CA E545K mutant TCCSUP cells had an IC 50 as low as 1 μM. These observations are consistent with previous studies that suggested sensitivity to PI3K inhibitors was dependent on hotspot PIK3CA mutation status (9,10,29). We also revealed that AKT phosphorylation in TCCSUP cells could be inhibited by pictilisib to a nadir after 30 minutes, while remaining measurable in resistant J82 and T24 cells.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The growth of five bladder cancer cell lines could be inhibited by pictilisib to some extent, but only PIK3CA E545K mutant TCCSUP cells had an IC 50 as low as 1 μM. These observations are consistent with previous studies that suggested sensitivity to PI3K inhibitors was dependent on hotspot PIK3CA mutation status (9,10,29). We also revealed that AKT phosphorylation in TCCSUP cells could be inhibited by pictilisib to a nadir after 30 minutes, while remaining measurable in resistant J82 and T24 cells.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, inhibiting this signaling pathway may facilitate chemotherapy treatments (7,8). Preclinical studies and early clinical trials indicate that the treatment of several cancers including breast (9), lung (10), medulloblastoma (11), and pancreatic cancer (6) could benefit from PI3K inhibitors. It is plausible that such targeted therapeutic approaches against the PI3K/AKT pathway can be used in patients with advanced bladder cancer, either as a single agent or in combination, to decrease drug resistance and augment the efficacy of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, these cancers demonstrate a predictable pattern of loss of tumor suppressors RB and p53 in almost all cases, and loss of PTEN or PIK3CA mutations in up to 20% of cases (3, 4). In addition, we have previously demonstrated that BCL-2, the founding pro-survival BCL-2 family member, is highly expressed in 65% of cases (5, 6), as is BIM (7), a pro-apoptotic BCL-2 family member which sensitizes SCLC to targeted therapies, in particular BH3 mimetics (8).…”
Section: Introductionmentioning
confidence: 99%
“…Except for TP53 , the percentage of tumors with either one of these driver mutations is less than 25%(2,3). Another recurrent event found in non-small cell lung cancers (NSCLC) and small cell lung cancers (SCLC) is activation of the PI3K/AKT pathway (3–5), which is frequently caused by loss of PTEN (6). Because of this confusing abundance of genetic mutations and other genetic anomalies, it is difficult to pinpoint specific drivers in any given patient and many lung cancer genetic drivers have yet to be identified (7).…”
Section: Introductionmentioning
confidence: 99%